Primary cardiac B-cell lymphoma - Karakuş, Alper; Arı, Hasan; Arı, Selma; Çamcı, Sencer; Tütüncü, Ahmet (The European Research Journal, 2018)
Primary tumors of the heart are very uncommon and approximately 25% of them are malign. Primary cardiac lymphomas account for approximately 4% of the primary cardiac tumors. Both B- and T-cell lymphomas have been reported. We report the case of a 75-year-old male who was referred to our hospital complaining of fatigue, dyspnea and swelling in the abdomen. Transthoracic echocardiography revealed a mobile 5.0×4.3 cm mass in the right atrial cavity impinging tricuspid valve. Surgery was performed and the mass was resected. The pathological and histological examination of the removed mass showed diffuse large B-cell lymphoma.